2013
DOI: 10.2141/jpsa.0120145
|View full text |Cite
|
Sign up to set email alerts
|

Dietary L-carnitine Improves Pulmonary Hypertensive Response in Broiler Chickens Subjected to Hypobaric Hypoxia

Abstract: The present study was conducted to examine the effects of L-carnitine on pulmonary hypertensive response in broiler chickens reared at high altitude and exposed to hypobaric hypoxia. A total of 192 day-old male broilers (Cobb 500) were randomly assigned to 4 treatments and 4 replicates of 12 chicks. A basal diet composed of mainly corn and soybean meal was formulated and served as a control. Three additional treatments were made by supplementing graded levels of L-carnitine (50, 100, and 150 mg/kg). Chicks rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
4
12
0
Order By: Relevance
“…Reactive oxygen species cause damage to cell membranes. Previous reports (Tan et al, 2008;Yousefi et al, 2013) further support this observation. Tan et al (2008) indicated that addition of a 100 mg/kg L-carnitine supplement to the diet resulted in significantly lower plasma MDA in broiler chickens.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Reactive oxygen species cause damage to cell membranes. Previous reports (Tan et al, 2008;Yousefi et al, 2013) further support this observation. Tan et al (2008) indicated that addition of a 100 mg/kg L-carnitine supplement to the diet resulted in significantly lower plasma MDA in broiler chickens.…”
Section: Discussionsupporting
confidence: 81%
“…Tan et al (2008) indicated that addition of a 100 mg/kg L-carnitine supplement to the diet resulted in significantly lower plasma MDA in broiler chickens. Yousefi et al (2013) demonstrated that plasma MDA concentration was significantly decreased by dietary supplementation of L-carnitine ranging from 50 to 150 mg/kg of diet in broiler chickens. Inhibition of ROS generation or scavenging of ROS has been shown to inhibit the hypoxiainduced proliferation in the pulmonary vasculature and, consequently, pulmonary hypertension (Springer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the interim, CoQ 10 alone or with combination of TAU plunged ascites mortality to levels even lower that the control. There is a great deal of evidence on the role of CoQ 10 in cardiometabolic disorders (Zozina, Covantev, Goroshko, Krasnykh, & Kukes, 2018) and pulmonary arterial hypertension (Sharp et al, 2014;Yousefi, Khajali, Hassanpour, & Khajali, 2013) through improved mitochondria function and enhanced NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Eight chicks per treatment were randomly selected at day 40 and electrocardiograms (ECG) were recorded. The electrocardiograph (Kenz ECG 110, SUZUKEN CO., LTD. Nagoya, Japan) was standardized at 10 mm=1 mV with a chart speed of 50 mm/s (Hassanpour et al, 2009;Yousefi et al, 2013). Leads II was recorded for every chicken, and the amplitude of the T, R and S waves were measured.…”
Section: Electrocardiographic Recordingmentioning
confidence: 99%
“…Rodehutscord et al (2002) reported that LC supplement (80 mg/kg) did not significantly improve the efficiencies of energy and protein utilization, suggesting LC may have other important biological impacts. Yousefi et al (2013) indicated that LC supplement (100 mg/kg) increased circulatory level of nitric oxide (NO), an important cellular signaling molecule involved in many physiological processes. Nitric oxide is also a powerful vasodilator that prevents pulmonary hypertension (Izadinia et al, 2010;Khajali et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%